Endoscopic sleeve gastroplasty: suturing the gastric fundus does not confer benefit - Farha, Jad; McGowan, Christopher; Hedjoudje, Abdellah; Itani, Mohamad I.; Abbarh, Shahem; Simsek, Cem; Ichkhanian, Yervant; Vulpis, Trish; James, Theodore W.; Fayad, Lea; Khashab, Mouen A.; Oberbach, Andreas; Badurdeen, Dilhana; Kumbhari, Vivek (Endoscopy, 2020)
Background There is heterogeneity regarding the technical aspects of endoscopic sleeve gastroplasty (ESG), such as applying fundal sutures. Our aim was to determine whether ESG with fundal suturing (ESG-FS) affects weight loss and the serious adverse event (SAE) rate when compared with ESG with no fundal suturing (ESG-NFS).Methods We conducted a two-center retrospective analysis of 247 patients who underwent ESG with or without fundal suturing. The primary outcome was percentage excess weight loss (%EWL) at 3, 6, and 12 months post-ESG. The secondary outcomes included the SAE rate and procedure duration.Results At 3, 6, and 12-months, ESG-NFS had a significantly greater mean %EWL compared with ESG-FS (38.4 % [standard deviation (SD) 15.3 %] vs. 31.2 % [SD 13.9 %], P = 0.001; 54.7 % [SD 19.2 %] vs. 37.7 % [SD 17.3 %], P < 0.001; 65.3 % [SD 21.1 %] vs. 40.6 % [SD 23.5 %], P < 0.001, respectively). There was no statistically significant difference in the SAE rates for ESG-NFS (n = 2; 2.0 %) and ESG-FS (n = 4; 2.6 %; P > 0.99). The mean procedure time was significantly shorter in the ESG-NFS group at 59.1 minutes (SD 32.7) vs. 93.0 minutes (35.5; P < 0.001), and a lower mean number of sutures were used, with 5.7 (SD 1.1) vs. 8.4 (SD 1.6; P < 0.001).Conclusion ESG-NFS demonstrated greater efficacy and shorter procedure duration. Therefore, fundal suturing should not be performed.